Optic disc morphology in primary open-angle glaucoma versus primary angle-closure glaucoma in South India - Parikh, Rajul; Kitnarong, Naris; Jonas, Jost B.; Parikh, Shefali R.; Thomas, Ravi (Indian journal of ophthalmology, 2021)
Purpose: - The aim of this study was to investigate the optic disc morphology in primary angle-closure glaucoma (PACG) versus primary open-angle glaucoma (POAG) in South Indians. - Methods: - A total of 60 patients (60 eyes) with PACG and 52 patients (52 eyes) with POAG were included in a cross-sectional observational study. The glaucoma diagnosis was based on a glaucomatous appearance of the optic disc correlating with visual field defects. The glaucoma was graded as early, moderate, or severe, depending upon perimetric loss. All patients underwent an ophthalmic evaluation, including visual field examination and planimetric analysis of 30° stereoscopic color optic disc photographs. - Results: - The POAG and PACG groups did not differ significantly in a disc or rim area, rim width, and frequencies of disc hemorrhages or rim notches. However, early POAG group (n = 15) had a significantly deeper cup depth (P = 0.01), larger beta zone (P = 0.01), and a higher frequency of localized retinal nerve fiber layer (RNFL) defects (P = 0.02) than early PACG (n = 20). - Conclusion: - In the early stage of the disease, POAG compared to PACG may be characterized by deeper disc cupping, a larger beta zone of peripapillary atrophy, and a higher frequency of localized RNFL defects. Such differences in early glaucoma may suggest differences in pathophysiology in POAG and PACG.
Gesehen am 10.06.2022